Experimental study on the importance of improving physical training in middle-distance and long-distance track running trials - Dobre, A. G.; Bondoc-Ionescu, D.; Mereuta, C. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2017)
All the fields and aspects of athletics and sport training are characterised by the occurrence of various progression and perfection elements, innovative elements, but also by updating and adjusting to superior parametres. The competition for all the levels of performance is very tight and numerous specialists investigate and select the latest information, from various fields of activity, to adjust them to athletics, in the hope that they might become means and measures to improve and perfect the sport area and the training procedure. Physical training for athletes is highly superior to physical training specific to other sports and covers two aspects: general or multilateral physical training and specific or special physical training. The purpose of this study is to highlight the importance of the improvement of physical training for middle-distance and long-distance running athletes. Starting from the idea that performance is achieved subsequent to a very well developed training process, comes the hypothesis according to which there is a possibility of improving the sport performance of middle-distance and long-distance running athletes by perfecting the physical training on a daily basis. Physical training in the service of specificity must serve the conditions of achieving the sport task, taking into account the psychomotor aspects connected to learning the technique, the functional means connected to their improvement and the energetic scale connected to the trial (specific intensity and resistance).After taking a series of initial tests, (800 m, 1000 m, 3000 m), we shall act to this purpose with the specific athletics means, adequately adapted to a period of 3 months, during the training of performance athletes (juniors 1), registered at the University Sport Club, in Galati.